Internet Banking: Content Analysis of Selected Indian Public and Private Sector Banks’ Online Portals - Tejinderpal, S.; Kaur, Manpreet (ARRAY Development, 2012)
Advancement in technology has played an important role in the distribution strategy of commercial banks. Banks distribute their products and services not only through a sole channel but instead through a variety of channels such as internet banking, automated teller machines, mobile banking, phone banking, TV baking etc. Internet banking has attracted the considerable amount of interest of researchers in the recent times. Previously research studies had concentrated on the perception about online service quality, adoption of internet banking, impact of information technology in banking, etc. based on customers’ opinion. However, on the other side, in depth analysis of bank’s online portal without approaching the customers may also provide meaningful insight about the online portals especially when compared with other banks’ online portals. The present study aims to compare the pre-login and after login features of selected banks’ online portals. For study purpose, two leading banks, one each from public and private sector were selected. A content analysis technique was used to study the listed features of selected websites. Study found that selected banks’ online portals differ on various features such as accounts information, fund transfer, online requests and general information. In the end, study suggested to include the good feature of other online portal which would help them to make their sites more secure, informative and user friendly.